2021
DOI: 10.1371/journal.pone.0247957
|View full text |Cite
|
Sign up to set email alerts
|

Health and wellbeing of indigenous older adults living in the tea gardens of Bangladesh

Abstract: Background There are currently 1.5 million indigenous people in Bangladesh, constituting 1.8% of the total population and representing one of the country’s most deprived communities. This study explores the health status and quality of life along with their determinants among indigenous older people in Bangladesh in order to fill the knowledge and evidence gap on this topic. Methods A mixed-methods approach was deployed in October 2019 in the Sylhet division of Bangladesh which involved a cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, there are other small-scale surveys on older adults (≥ 60 years) which have been addressing aging and health aspects in Bangladesh (Tareque et al, 2013 a, 2013b ; Tareque et al, 2014 , 2015a , 2015b ). These studies showed the prevalence of multimorbidity in older adults ranges from 56 to 80%, with hypertension, diabetes, ischemic heart disease, chronic obstructive pulmonary disease, and visual impairment being predominant (Rahman et al, 2021 ; Sara et al, 2018 ). Women (versus men) reported a higher disability, with 34.8% of women aged 60–64 years with at least one disability (Tareque et al, 2017 , 2013a , 2013b ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other small-scale surveys on older adults (≥ 60 years) which have been addressing aging and health aspects in Bangladesh (Tareque et al, 2013 a, 2013b ; Tareque et al, 2014 , 2015a , 2015b ). These studies showed the prevalence of multimorbidity in older adults ranges from 56 to 80%, with hypertension, diabetes, ischemic heart disease, chronic obstructive pulmonary disease, and visual impairment being predominant (Rahman et al, 2021 ; Sara et al, 2018 ). Women (versus men) reported a higher disability, with 34.8% of women aged 60–64 years with at least one disability (Tareque et al, 2017 , 2013a , 2013b ).…”
Section: Discussionmentioning
confidence: 99%
“…These ethnic groups have long maintained isolation from the general population, putting them at a disadvantage in obtaining healthcare facilities. As a consequence, their overall health status remains poorer compared with non-indigenous people 34–36. There is not sufficient information regarding antibiotics usage, including SMA, among this community of more than 2 million people.…”
Section: Introductionmentioning
confidence: 96%
“…Through a comprehensive literature review, we found several relevant studies on healthcare challenges faced by indigenous populations in Bangladesh. These included research by Saha et al (2022) [43] , on the prevalence of self-medication and its impact among indigenous communities in the Chittagong hill track area, Rahman et al (2021) [44] , on the health status and quality of life of older indigenous individuals in the Sylhet region, studies on the challenges of maternal healthcare access for indigenous women [45] and research by Lewis and Myhra (2018) on healthcare disparities in rural areas affecting indigenous populations [46] .…”
Section: Introductionmentioning
confidence: 99%